The Context of Professionalism among Early Childhood Education Teachers in Indonesia (PIAUD IAIN Kudus, 2023)
The teacher is be told a professional teacher when he has basic competence as a teacher. The purpose of this research is to find out and analyze in the professional context of early childhood teachers in Indonesia. Data collection was carried out using qualitative research methods. Data collection is useful for obtaining the information needed to achieve research objectives. Data collection was carried out by distributing questionnaires to 34 early childhood education teachers in Indonesia as respondents based on length of teaching. The results of the Professional Good Teacher research in the Context of Early Childhood Teachers in Indonesia concluded that a professional good teacher can be said if the teacher fulfills, 1) the requirements of a professional teacher; 2) have professional teacher competence; 3) have good ethics as a professional teacher; 4) teachers who meet National Standards (Law Number 20 of 2003) and International Standards (National Association for Early Young Children), and; 5) teachers who are linear in their fields, for example early childhood education teachers, the linear study is early childhood education. With the existence of government standards and regulation related to early childhood education professional teachers, it can be improved and developed so as to achieve quality education.